2019
DOI: 10.17509/ijal.v8i3.15270
|View full text |Cite
|
Sign up to set email alerts
|

How do students become self-directed learners in the EFL flipped-class pedagogy? A study in higher education

Abstract: The purpose of this study was to identify the impact of implementing a Learning Management System (LMS) ‘TES BlendSpace’ to promote students’ self-directed learning in EFL flipped-class instruction. For the data collection procedure, an individual interview with ten undergraduate students from an Indonesian college was conducted to demonstrate the potential impacts of the LMS in students’ self-directed learning abilities. The observation of students’ learning activities on the TES BlendSpace was also recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
87
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 17 publications
9
87
1
10
Order By: Relevance
“…The present study intends to confirm the effectiveness that flipped learning has obtained in the field of educational research as reported in the recent impact literature [7,11,13,49,50,[73][74][75]. This effectiveness has been contrasted with the classical and expository methods of knowledge transmission, where the teacher reproduces the contents unilaterally without encouraging the exchange of knowledge and interaction with students [76].…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…The present study intends to confirm the effectiveness that flipped learning has obtained in the field of educational research as reported in the recent impact literature [7,11,13,49,50,[73][74][75]. This effectiveness has been contrasted with the classical and expository methods of knowledge transmission, where the teacher reproduces the contents unilaterally without encouraging the exchange of knowledge and interaction with students [76].…”
Section: Introductionsupporting
confidence: 68%
“…The didactic contents taught were related to statistics, graphic representations, and problem solving. In this way, in the different sessions, the following didactic objectives were worked through: (a) to know the scientific language and concepts of statistics (sessions 1-2); (b) to understand the fundamental principles for data processing and scientific processes (sessions 3-4); (c) to acquire skills in statistical analysis and representation of graphs (sessions 5-8); (d) to assimilate skills in the interpretation and reflection of results (sessions 7-10); and (e) to develop skills for correct decision-making (sessions [11][12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a situation, the flipped-classroom pedagogical model is one of the alternatives implemented as the effort to ensure students get more exposure and much time to practice the language (Li & Suwanthep, 2017). A flipped classroom is often defined as the inverted classroom in which the lecture content is learned at home in the form of videolecture while the homework or task is done at school (Bergmann & Sams, 2012;Chuang, Weng, & Chen, 2018;Zainuddin, Habiburrahim, Muluk, & Keumala, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this innovative pedagogy tries to change the way teachers taught by converting what traditionally occurs both in and out of the classroom (Jacob, & Matthew, 2013;Zainuddin et al, 2019). Unlike other conservative classrooms where the teacher becomes the Sage of the Stage in a lecture-based class, the flipped classroom allows the teacher to be the Guide on the Side in an activitybased class allowing students to be more active and interactive.…”
Section: Introductionmentioning
confidence: 99%